Prevalence and incidence of autoimmune pancreatitis in the population living in the southwest of Germany - Schneider, Alexander; Michaely, Henrik J. M.; Weiß, Christel; Hirth, Michael; Rückert, Felix; Wilhelm, Torsten; Schönberg, Stefan; Marx, Alexander; Singer, Manfred V.; Ebert, Matthias; Pfützer, Roland (Digestion, 2017)
Background/Aims: The prevalence and incidence of autoimmune pancreatitis (AiP) in those living in western countries are largely unknown. We aimed to determine the prevalence of AiP among patients with pancreatitis presenting to our tertiary referral center in Mannheim, Germany; and to estimate the incidence of AiP in the Southwest of Germany. Methods: We performed a retrospective cross-sectional analysis and determined the prevalence of AiP in patients with acute pancreatitis (AP) or chronic pancreatitis (CP). Patients (n> = 704; alcoholic pancreatitis n = 373, nonalcoholic pancreatitis n = 331) were stratified into the Retrospective-Pancreas-Cohort (RPC, period 1998-2008, n = 534) and the Pancreas-Clinic-Cohort (PCC, periods 2008-2010 and 2013-2014, n = 170, with detailed investigation for features of AiP). Diagnosis of AiP was established by International-Consensus-Diagnostic-Criteria and Unifying-Autoimmune-Pancreatitis-Criteria. Results: In the RPC, the prevalence of AiP was 5.9% (n = 13/221) among individuals with nonalcoholic pancreatitis (n = 1/61 with AP, 1.6%; n = 12/160 with CP, 7.5%). In the PCC, the prevalence of AiP was 9.1% (n = 10/110) among patients with nonalcoholic pancreatitis (n = 2/24 with AP, 8.3%; n = 8/86 with CP, 9.3%), and 1.7% (n = 1/60) among subjects with alcoholic pancreatitis. We estimated the incidence of AiP with 0.29 per 100,000 population each year. Conclusion: The prevalence rate of AiP may account for 9% of patients with nonalcoholic pancreatitis but is almost never observed in patients with alcoholic pancreatitis. The incidence of AiP in Germany appears lower than 1 per 100,000 population.